Corona is required for higher-order assembly of transverse filaments into full-length synaptonemal complex in Drosophila oocytes. - Scott L Page; Radhika S Khetani; Cathleen M Lake; Rachel J Nielsen; Jennifer K Jeffress; William D Warren; Sharon E Bickel; R Scott Hawley (PLoS Genetics, 2008)
The synaptonemal complex (SC) is an intricate structure that forms between homologous chromosomes early during the meiotic prophase, where it mediates homolog pairing interactions and promotes the formation of genetic exchanges. In Drosophila melanogaster, C(3)G protein forms the transverse filaments (TFs) of the SC. The N termini of C(3)G homodimers localize to the Central Element (CE) of the SC, while the C-termini of C(3)G connect the TFs to the chromosomes via associations with the axial elements/lateral elements (AEs/LEs) of the SC. Here, we show that the Drosophila protein Corona (CONA) co-localizes with C(3)G in a mutually dependent fashion and is required for the polymerization of C(3)G into mature thread-like structures, in the context both of paired homologous chromosomes and of C(3)G polycomplexes that lack AEs/LEs. Although AEs assemble in cona oocytes, they exhibit defects that are characteristic of c(3)G mutant oocytes, including failure of AE alignment and synapsis. These results demonstrate that CONA, which does not contain a coiled coil domain, is required for the stable 'zippering' of TFs to form the central region of the Drosophila SC. We speculate that CONA's role in SC formation may be similar to that of the mammalian CE proteins SYCE2 and TEX12. However, the observation that AE alignment and pairing occurs in Tex12 and Syce2 mutant meiocytes but not in cona oocytes suggests that the SC plays a more critical role in the stable association of homologs in Drosophila than it does in mammalian cells.